The handbook of systemic family therapy. (Wiley-Blackwell, 2020)
Volume II of The Handbook of Systemic Family Therapy presents established and emerging models of relational treatment of children and young people. Developed in partnership with the American Association for Marriage and Family Therapy (AAMFT), it will appeal to clinicians, such as couple, marital, and family therapists, counselors, psychologists, social workers, and psychiatrists. It will also benefit researchers, educators, and graduate students involved in CMFT.